Analysis of antecedents and consequences of workplace-related burnout among Croatian employees in the post-COVID-19 era - Moric Milovanovic, Bojan; Cvjetkovic, Matea (Business: Theory and Practice, 2024)
Employee burnout is considered a serious problem in today’s organizations, having severe repercussions both on individual and operational levels. A large number of studies have been conducted to identify antecedents and consequences of burnout but were mostly carried out in medical and other helping professions. This research aims to explore the burnout of employees working in Croatian companies by developing a multidimensional model that explores the influence of three elements that are considered typical features of today’s modern, post-pandemic workplace: information overload, demands at work, and multitasking. In addition, it observes the influence of burnout on employee decision-making style and the moderating effects of information accuracy and time pressure on the burnout-decision-making relationship. A total of 567 employees working in various industries and carrying out different professions completed an online survey, and linear regression analysis was applied to analyze the data. The results confirmed the direct positive effect of information overload and demands at work on burnout and the direct positive effect of burnout on poor decision-making style. This study is one of the first studies conducted in Croatia on employees in the business sector, so it contributes to the field with important theoretical implications and practical and managerial recommendations.